Non-destructive evaluation methods that can be used for the determination of some properties of historical wooden structures - Bilgin İçel (Turkish Journal of Forestry, 2016)
Wood as a natural, sustainable and renewable resource has been used for structural and engineering purposes in human life for thousands of years and still maintains its importance. Human beings have been used the wood and wooden products for both shelter and daily products which make their life more comfortable for ages. In our country, using wood as raw material in historical buildings is quite common in the past. There are many wooden architectures holdover from both Seljuk and the Ottoman periods in Anatolia. Aging and fatigue are natural results of wooden structures in time. Therefore, the material should be evaluated in terms of the resistance of material and necessity of any replacement when the wooden structure in the maintenance and restoration work. The conventional tests used to provide this information are required to take samples in certain sizes, but especially in cultural heritages, evaluation methods must be non-destructive. In such structures the general preference is for procedures without any sampling or limited sampling size and amount. Non-destructive evaluation (NDE) is the only way to meet this. In this study some Nondestructive Testing-Evaluation Methods, that can be applied in order to estimate some properties especially physical, mechanical and acoustic properties of wood in the historic wooden structures, introduced.